Improve student competence of light vehicle engineering expertise program according to industrial needs - Pramono, Edy; Suhartadi, Syarif; Yoto, Yoto (Journal of Research in Instructional, 2023)
This activity intends to encourage the implementation of the "Freedom to Learn" program promoted by the Indonesian government. Vocational school students are prepared to learn skills so that graduates have the qualifications expected by the world of work according to their respective fields. In this case, Vocational High Schools can adjust the industrial work culture so that students, when they graduate, can adjust the fields studied appropriately. This research method is qualitative research. Data collection techniques used interview, observation, and documentation methods in this research. The data analysis technique uses the triangulation test. From the research results, seven students could get good car service, and one student did not do well. In implementing the 5R/S work culture, eight students all did well. Time to complete the work: 2 students completed over 60 minutes, and six students under 60 minutes. With these results, special treatment is needed, namely doing a lot of car service work regularly, to improve the results obtained. This work takes approximately 30 – 45 minutes to complete for industry standards.